Star wars: the mandalorian (2022), season one, part two ebook - Barnes, Rodney (Star Wars: The Mandalorian (2022), 2023)
Collects STAR WARS: THE MANDALORIAN #5-8. The comic book adaptation of the hit series continues! A rookie bounty hunter needs a little help with a tough job, and who better than the Mandalorian to lend his expertise? But when Mando finds himself allied with a ragtag crew of cutthroat mercenaries looking to spring a convict from a prison ship, the mission will turn out to be far more difficult - and deadly - than it appeared! As an old rival offers an olive branch, the Mandalorian welcomes the chance to enjoy a little peace - but before long, he finds himself cornered by powerful enemies. One of them knows all about the Mandalorian's past - and is determined to make sure he has no future! But when the dust settles on this conflict, what will be the fate of the Child?